(untitled) (Bioagro, 2020)
The control of tuber sprouting and the behavior of bioactive compounds during postharvest storage is of importance for the Andean communities that cultivate these tubers. Therefore, this work evaluated the effect of Chlorpropham (CIPC) on purple mashua tubers during postharvest storage. Purple mashua tubers from the Paucará district, Acobamba province (Peru) were used, which were randomly collected and placed in cardboard boxes covered with plastic. Subsequently, the concentration of 10, 20 and 30 mg·kg-1 of CIPC were applied, plus a control treatment without application. The measurements included the length of sprout, weight loss percentage, anthocyanin content, content of phenolic compounds, and antioxidant capacity at 0, 30, 60 and 90 days of storage. It was found that the application of CIPC and the time of storage affected the growth of shoots and the content of bioactive compounds in the tubers. The CIPC did not inhibit the formation of shoots but caused a reduction in their length and a decrease in the percentage of weight loss of the tubers, and this effect was greater with the higher doses of the product. As the storage time increased, the anthocyanin content was reduced and the content of phenolic compounds in the tubers increased regardless of the dose of the CIPC. In all evaluations, the increase in the product doses caused an increase in anthocyanins and a reduction in phenolic compounds. In general, the antioxidant capacity tended to increase over time, although with marked reductions with the higher doses of CICP.